Leachability of Fired Clay Bricks Incorporated with Sewage Sludge by Using Tank Leaching Test - Salim, Nurul Salhana Abdul; Kadir, Aeslina Abdul; Kamarudin, Mohamad Asyraf; Zaidi, Mohd Hafizul Fadzli (International Journal of Engineering and Technology, 2018)
This research was conducted to fully utilize the sludge that rich in dangerous heavy metals and at the same time act as low cost alternative materials in brick manufacturing. Different series of sludge and clay proportioning ratios were studied, which exclusively involved the addition of sludge with ratios of 0, 1, 5, 10, 20 and 30% of the total weight of sludge-clay mixture. Each molded brick were oven-dried at 105ËšC for 24 hours followed by heating at 1050ËšC. The investigation includes determination of heavy metal concentration of the sludge and clay using XRF and heavy metals leachability of the bricks by using Tank Leaching Test according to NEN7345 that has been analyzed by using ICPMS. The leaching behavior of several heavy metals (As, Ni, Cu, Pb, Zn, V, Ba, and Cr) from incorporated sludge into fired clay bricks shows to be insignificant and far below the USEPA regulations limits which fulfill the general requirement for usage of clay brick in construction and comply with the leaching standard limit. As a conclusion, the utilization of sewage sludge can reduce the disposal to landfill and reduce the leachability of sludge which can effect environment and human.